Protein coding identification using modified gabor wavelet transform on multicore system - Gunawan, Teddy Surya (IIUM Press, 2011)
The gene identification problem, which identifies the protein-coding regions (exons) in DNA sequences through computational means, is of great importance nowadays. A DNA sequence can be divided into genes and intergenic spaces. In eukaryotic genes, these regions can be divided into two sub-regions called coding regions (exons) and non-coding regions (introns). The intergenic and intronic regions make up most of the genome. For example, in the human genome, the exonic fraction is as low as 2%. It is well known that protein-coding regions of DNA sequences tend to exhibit a period-3 pattern because of the codon structure involved in the translation of base sequences into amino acids [1-4]. Many researchers have regarded the period-3 property to be a good indicator ofgene location.